The effect of seed processing management on the quality parameters of corn (Zea mays L.) hybrid single cross 704 in Moghan region - Ramin Soltani; Jafar Asghari; Enayat Rezvani; Babak Rabiei (علوم و فناوری بذر ایران, 2024)
Considering the questions about the reasons for the decline in the quality of corn seeds in Moghan, especially regarding the management of corn cob dryers, this experiment was conducted in order to diagnose the effect of the dryer function on seed quality. For this purpose, 24 samples of corn seed variety 704 were prepared in two stages from nine seed processing stations in 2018. 12 cobs from the shipment were transported from the field and before entering the dryer and 12 dried cobs of the same shipment were randomly registered and tested in the National Seed Quality Laboratory. In addition to laboratory tests, each sample was cultivated in the field in the form of a RCBD in three replications. According to the results there is no significant difference between the sampling time before and after drying. The interaction of processing station and sampling time, except in two stations, did not show any significant difference on seed quality indicators. Based on the results, in the stations with higher output seed quality, the cobs were harvested with a moisture content of 25-29% and aerated at a temperature of 32-35℃ and after reaching the average moisture content of the mass about 20%, the temperature increased to 38℃. According to the results, the dryers function has a minor role in causing damage to seeds and reducing seed quality, and due to the low germination power of seeds produced in farms, other factors including farm management are effective in reducing the quality of corn seeds.